Phytohormonal regulation of the development of Dryopteris filix-mas (L.) Schott gametophyte in vitro culture - Romanenko, K.O.; Babenko, L.M.; Vasheka, O.V.; Romanenko, P.O.; Kosakivska, I.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
Effects of exogenous cytokinin phytohormones such as kinetin, zeatin, 6-benzylaminopurine, and N6-2-isopentenyladenine on the gametophyte morphology and growth features of Dryopteris filix-mas (L.) Schott in vitro culture have been studied. It is established that, at the concentration of 10−5 M, all studied cytokinins inhibit the gametophyte growth, cause deformations and changes in the thallus size, and suppress the development of reproductive structures and sporophyte growth. Reduction of the hormone concentration to 10−8 M stimulates the gametophyte development, induces cell divisions, particularly in the apical zone, due to which some of thalli are deformed, promotes the production of rhizoids, affects the formation of antheridia and archegonia, and slows the sporophyte development.